Human cardiosphere-derived stromal cells exposed to SARS-CoV-2 evolve into hyper-inflammatory/pro-fibrotic phenotype and produce infective viral particles depending on the levels of ACE2 receptor expression. Issue 6 (10th March 2021) - Amendola, Alessandra; Garoffolo, Gloria; Songia, Paola; Nardacci, Roberta; Ferrari, Silvia; Bernava, Giacomo; Canzano, Paola; Myasoedova, Veronika; Colavita, Francesca; Castilletti, Concetta; Sberna, Giuseppe; Capobianchi, Maria Rosaria; et al.
Abstract: Aims: Patients with severe respiratory syndrome caused by SARS-CoV-2 undergo cardiac complications due to hyper-inflammatory conditions. Although the presence of the virus has been detected in the myocardium of infected patients, and infection of induced pluripotent cell-derived cardiomyocytes has been demonstrated, the reported expression of Angiotensin-Converting Enzyme-2 (ACE2) in cardiac stromal cells suggests that SARS-CoV-2 may determine cardiac injury by sustaining productive infection and increasing inflammation. Methods and results : We analysed expression of ACE2 receptor in primary human cardiac stromal cells derived from cardiospheres, using proteomics and transcriptomics before exposing them to SARS-CoV-2 in vitro . Using conventional and high sensitivity PCR methods, we measured virus release in the cellular supernatants and monitored the intracellular viral bioprocessing. We performed high-resolution imaging to show the sites of intracellular viral production and demonstrated the presence of viral particles in the cells with electron microscopy. We finally used RT–qPCR assays to detect genes linked to innate immunity and fibrotic pathways coherently regulated in cells after exposure to the virus. Conclusions : Our findings indicate that cardiac stromal cells are susceptible to SARS-CoV-2 infection and produce variable viral yields depending on the extent of cellular ACE2 receptor expression. Interestingly, these cells also evolved towards hyper-inflammatory/pro-fibrotic phenotypes independently of ACE2 levels. Thus, SARS-CoV-2 infection of myocardial stromal cells could be involved in cardiac injury and explain the high number of complications observed in severe cases of COVID-19.